Dendrochronology and absolute dating of pile-dwellings in Ljubljansko Barje - Čufar, Katarina (Les (Ljubljana), 2022)
Between 1995 and 2021, archaeological excavations at 16 sites in Ljubljansko barje, Slovenia, collected more than 8,800 samples of waterlogged archaeological wood, mostly from piles driven into the ground on which dwellings were built. About 20% of the samples were from oak (Quercus sp.) and ash (Fraxinus sp.) trees with more than 45 tree-rings, which could be included in the dendrochronological analyses, and tree-ring chronologies could be established for most sites. Dating by dendrochronology, radiocarbon dating, and wiggle matching, as well as teleconnection with the German-Swiss reference chronology, allowed absolute dating of oak in the time frame 3771–3330 BC (BAR-3330 chronology), while precise 14C dates were obtained for chronologies covering the periods 3285–3109 ± 14 cal BC (SG-VO) and 2659–2417 ± 18 cal BC (ZA-QUSP1). The potential of the ash wood chronologies, especially those of the 3rd millennium BC, when this wood species was predominant, has not yet been fully exploited.
Keywords: absolute dating; absolutno datiranje; archaeological wood; arheološki les; C14 wiggle-matching; dendrochronology; dendrokronologija; eneolithic; eneolitik; koliščarske naselbine; Ljubljansko barje; neolithic; neolitik; pile dwellings; radiocarbon wiggle-matching